Pengembangan Bahan Ajar IPS Terintegrasi Pendidikan Lingkungan Hidup pada Mata Kuliah Konsep Dasar IPS - Musyarofah Musyarofah; Abdurrahman Ahmad (heritage, 2021)
The purpose of this research are: (1) To describe the development of integrated social studies teaching materials for environmental education in the basic concepts of social studies in the IPS Tadris Study Program of IAIN Jember (2) to describe the feasibility of developing integrated social studies teaching materials for environmental education in the concept course Basic IPS in Social Studies Tadris Study Program IAIN Jember. This type of research is a research and development (R&D) model modified from the Borg & Gall (2003) model. The results showed that the teaching materials had the feasibility of material experts, design experts and linguists which meant that the teaching materials were valid or suitable for use. The Development of Integrated Social Studies Teaching Materials for Environmental Education in the Basic Concepts of Social Studies in the Social Studies Tadris Study Program at IAIN Jember consists of 6 subjects / chapters. While the test results of the effectiveness of teaching materials by looking at student learning outcomes, show that the average student learning outcomes are able to obtain the minimum average value limit of the completeness of the value of knowledge in learning.